Resting-state functional MRI of the nose as a novel investigational window into the nervous system - Ponticorvo, Sara; Paasonen, Jaakko; Stenroos, Petteri; Salo, Raimo A; Tanila, Heikki; Filip, Pavel; Rothman, Douglas L; Eberly, Lynn E; Garwood, Michael; Metzger, Gregory J; Gröhn, Olli; Michaeli, Shalom; et al. (Scientific reports, 2024)
Besides being responsible for olfaction and air intake, the nose contains abundant vasculature and autonomic nervous system innervations, and it is a cerebrospinal fluid clearance site. Therefore, the nose is an attractive target for functional MRI (fMRI). Yet, nose fMRI has not been possible so far due to signal losses originating from nasal air-tissue interfaces. Here, we demonstrated feasibility of nose fMRI by using novel ultrashort/zero echo time (TE) MRI. Results obtained in the resting-state from 13 healthy participants at 7T and in 5 awake mice at 9.4T revealed a highly reproducible resting-state nose functional network that likely reflects autonomic nervous system activity. Another network observed in humans involves the nose, major brain vessels and CSF spaces, presenting a temporal dynamic that correlates with heart rate and breathing rate. These resting-state nose functional signals should help elucidate peripheral and central nervous system integrations.
Keywords: Young Adult; mapování mozku; Male; magnetická rezonanční tomografie; mladý dospělý; Brain; Autonomic Nervous System; Heart Rate; Adult; dospělí; mužské pohlaví; srdeční frekvence; Rest; Nose; odpočinek; autonomní nervový systém; Animals; Brain Mapping; lidé; ženské pohlaví; Humans; nos; zvířata; myši; mozek; Magnetic Resonance Imaging; Mice; Female